Africa RISING-Effects of P-Fertilizer Rates on Groundnut Yield in Northern Ghana - International Institute of Tropical Agriculture; Ministry of Food and Agriculture, Government of Ghana; Savanna Agricultural Research Institute (International Food Policy Research Institute, 2015)
Project title: Africa RISING-Effects of P-Fertilizer Rates on Groundnut in Northern Ghana. Project abstract: The data set evaluates adaptability and suitability of groundnut varieties to different ecozones. Project website: http://africa-rising.net http://africa-rising.net/where-we-work/west-africa/